FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBIASAAN MEROKOK DALAM RUMAH - Dina Ediana; Novia Sari (Jurnal Endurance, 2021)
Cigarette consumption in Indonesia in 2008 spent 240 billion cigarettes.an estimated 150 million teenagers smoke cigarettes and this number increases year by year. Data the Solok city health office, the cec community health center has the most people smoking (57.4%). This study aims to determine the factors associated smoking habits in the KTK Solok. Research methodology analytical descriptive with cross sectional study a sample of 244 heads with simple random sampling. The results of the study there were (54.1%) respondents with low knowledge (52.0%) respondents with negative advertising influence (54.1%) respondents with the role of families who were less involved, (52.9%) respondents with roles health workers who don’t play a role (55.7%) respondents who have smoking habits. Statistical tests have a significant relationship between knowledge with smoking habits (p=0.040/OR 1.7),the role of families with smoking habits (p=0.040/OR 1,7). the role of health workers with smoking habits (p=0.050/ OR 1.7) where as there is no relationship with smoking habits (p=0.224/OR 1.4) conclusions of knowledge, the role of the family and health workers are very influential with habits smoking. Expected to all family members to provide advice on the dangers of smoking in order to reduce smoking